Intra-Articular Administration of Tranexamic Acid in Total Hip Arthroplasty - Jerry Yongqiang Chen; Ngai Nung Lo; Darren Keng Jin Tay; Pak Lin Chin; Shi-Lu Chia; Seng Jin Yeo (Journal of Orthopaedic Surgery, 2015)
Purpose. To evaluate the effectiveness of intra-articular tranexamic acid (TXA) in reducing blood loss and the need for blood transfusion during total hip arthroplasty (THA). Methods. Records of 19 men and 31 women aged 46 to 83 (mean, 62) years who underwent primary THA with intra-articular administration of TXA were reviewed. They were compared with a matched cohort of 17 men and 33 women aged 40 to 87 (mean, 62) years who underwent the same procedure by the same surgeon without use of TXA. Postoperatively, a standard thromboembolic prophylaxis protocol was followed. A serum haemoglobin level of <80 g/l was the trigger for blood transfusion. Results. The 2 groups were comparable in terms of age, gender, body mass index, side involved, and anaesthesia method. No patient developed infection, wound haematoma, symptomatic deep vein thrombosis, or pulmonary embolism within 30 days. Compared with controls, patients in the TXA group had a higher median postoperative serum haemoglobin level (103 vs. 112 g/l, p=0.013), lower median drop in serum haemoglobin level (31 vs. 20 g/l, p<0.001), lower median total blood loss (900 vs. 575 ml, p<0.001), and lower transfusion rate (32% vs. 10%, p=0.007). The TXA treatment cost S$19.50 per patient, whereas one unit of allogenic blood cost S$123 per patient. Respectively in the control and TXA groups, the mean cost per patient was S$39.36 and S$31.80, indicating a 19% difference. Conclusion. Intra-articular administration of TXA is a cost-effective and safe means to reduce blood loss and the need for blood transfusion during THA, without increasing the risk of thromboembolic events.